Development of STEAM- Project Based Learning Module to Improve Numeracy Literacy of Upper Elementary School Students - Devi Triana Rahmadini; Pratiwi Kartika Sari (Mosharafa: Jurnal Pendidikan Matematika, 2025)
Tujuan penelitian yaitu mengembangkan modul STEAM berbasis Project Based Learning (PjBL) untuk meningkatkan literasi numerasi peserta didik kelas tinggi. Penelitian pengembangan model Borg and Gall ini mengadopsi 7 langkah yaitu research and information collecting, planning, develop preliminary from of product, preliminary field testing, main product revision, main field testing, operational product revision. Subjek penelitian yaitu peserta didik kelas IV SD meliputi 3 peserta didik pada uji one to one, 10 dalam uji small group, dan 26 dalam uji coba lapangan. Analisis kelayakan produk diperoleh dari hasil isian angket oleh ahli media, materi, bahasa, dan peserta didik pada skala one to one dan small group. Sedangkan analisis efektivitas diperoleh dari hasil pretest dan post test pada uji coba lapangan. Hasil uji validasi ahli media 98.5%, ahli materi 96% yang berarti produk sangat layak. Dari ahli bahasa diperoleh penilaian 76% termasuk kategori layak. Pada uji one to one diperoleh hasil 86% dan pada small group 90% termasuk kategori sangat layak. Hasil pretest dan post test pada uji coba lapangan diuji paired sample t-test. Diperoleh hasil 0.98 untuk pretest dan 0.97 untuk post test dengan p < .001, sedangkan N-Gain diperoleh yaitu 0.61  yang mana termasuk dalam kategori sedang. Dapat disimpulkan modul STEAM berbasis PjBL dapat meningkatkan literasi numerasi peserta didik kelas tinggi. This research aims to develop a STEAM-based Project Based Learning Instructional Module to improve numeracy literacy in upper-grade students. This developmental research using the Borg and Gall model, adopting seven steps: research and information gathering, planning, preliminary product developing, preliminary field testing, main product revising, main field testing, and operational product revising. The subjects were fourth-grade elementary school students: 3 students in the one-to-one test, 10 in the small-group test, and 26 in the field trial. The feasibility analysis was obtained from questionnaires completed by media, material, and language experts, as well as students on a one-to-one and small-group scale. The effectiveness analysis was obtained from the pretest and posttest results. The validation test results from the media expert were 98.5% and the material expert 96%, indicating the product was very feasible. The language expert received a 76% rating, categorizing it as feasible. In the one-to-one test, the results were 86% and in the small group, 90%, including the very feasible category. The results of the pretest and posttest in the field trial were tested the paired sample t-test. The results obtained were 0.98 for the pretest, and 0.97 for the posttest with p < .001, while the N-Gain obtained was 0.61 which is included in the moderate category. It can be concluded that the STEAM-based PjBL Instructional Module can improve the numeracy literacy of Upper Elementary School Students.